Multigene Assays for Classification, Prognosis, and Prediction in Breast Cancer: a Critical Review on the Background and Clinical Utility - Sinn, P.; Aulmann, S.; Wirtz, R.; Schott, S.; Marmé, F.; Varga, Z.; Lebeau, A.; Kreipe, H.; Schneeweiss, A. (Senologie - Zeitschrift für Mammadiagnostik und -therapie, 2014)
Gene signatures which are based on multigene profiling assays have been developed for the purpose to better define the prognosis and prediction of therapy results in early-stage breast cancer. These assays were designed to be more specific than conventional clinico-pathologic parameters in the selection of patients for (neo-)adjuvant treatment and in effect help to avoid unnecessary cytotoxic treatment. In this review we describe molecular risk scores, for which tests are commercially available (PAM50®, MammaTyper®, MammaPrint®, Oncotype DX®, Endopredict®, Genomic Grade Index®) and IHC risk scores (Mammostrat® and IHC4), and discuss the current evidence of their clinical use.
Keywords: breast cancer; multigene assays; prognosis